ChemInform Abstract: Access to New Endoperoxide Derivatives by Electrochemical Oxidation of Substituted 3‐Azabicyclo[4.1.0]hept‐4‐enes. Issue 34 (August 2015) - Nuter, Frederick; Dime, Abdou Khadre Djily; Chen, Cheng; Bounaadja, Lotfi; Mouray, Elisabeth; Florent, Isabelle; Six, Yvan; Buriez, Olivier; Marinetti, Angela; Voituriez, Arnaud
Abstract Cycloisomerization of substrates (I) or (V) in the presence of either a gold or a platinum catalyst leads to formation of fused pyridines such as (II) or (VI).